2014
DOI: 10.1098/rsif.2014.0399
|View full text |Cite
|
Sign up to set email alerts
|

The transition mechanism of DNA overstretching: a microscopic view using molecular dynamics

Abstract: The overstretching transition in torsionally unconstrained DNA is studied by means of atomistic molecular dynamics simulations. The free-energy profile as a function of the length of the molecule is determined through the umbrella sampling technique providing both a thermodynamic and a structural characterization of the transition pathway. The zero-force free-energy profile is monotonic but, in accordance with recent experimental evidence, becomes two-state at high forces. A number of experimental results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…This limitation results in the incapability of understanding why dsDNA twiststretch coupling changes with an applied force (2,3,32,33). An alternative approach computes potential(s) of mean force (PMF) (26,29,34). Nevertheless, obtaining a PMF where a given reaction coordinate (e.g., elongation, twist) is sampled enough to ensure thermal equilibrium is reached at each point is a very demanding computational task.…”
mentioning
confidence: 99%
“…This limitation results in the incapability of understanding why dsDNA twiststretch coupling changes with an applied force (2,3,32,33). An alternative approach computes potential(s) of mean force (PMF) (26,29,34). Nevertheless, obtaining a PMF where a given reaction coordinate (e.g., elongation, twist) is sampled enough to ensure thermal equilibrium is reached at each point is a very demanding computational task.…”
mentioning
confidence: 99%
“…Bianco et al (31) and Bongini et al (32) studied the transition kinetics of the overstretching transition using force-steps in pulling experiments of l-DNA (~48.5 kbp), where they found that the cooperative length of the B-to-S transition is~22-25 bp. The experimental findings of Bianco et al (31) and Bongini et al (32) have been recently satisfactorily reproduced using atomistic molecular-dynamics simulations (24).…”
Section: Introductionmentioning
confidence: 84%
“…Regardless of temperature T, length L, or ionic concentration I, for experimental curves where the change in extension is Lz 1:7 L the cooperativity of the system is given approximately by l˛ [22][23][24][25]bp. Although T, I, and L are different among the data sets presented in Fig.…”
Section: Cooperativity Length L Predictionsmentioning
confidence: 99%
See 2 more Smart Citations